Induction of abortion in the first trimester of pregnancy using letrozole and misoprostol combination versus misoprostol alone - A comparative observational study - Swarnali Biswas; Mallika Sengupta; Debdatta Ghosh; Rajesh De (Asian Journal of Medical Sciences, 2024)
Background: Medical abortion is safer than surgical abortion. Several studies have shown that combination of antiprogesterone drug mifepristone and prostaglandin misoprostol can increase complete abortion rate in medical management of first-trimester miscarriage compared to misoprostol alone. Letrozole, an aromatase inhibitor, has emerged as an alternative to mifepristone for induction of medical abortion as mifepristone is expensive and not registered in many countries. Aims and Objectives: The aim of the present study was to evaluate the safety and efficacy of combined regimen of letrozole and misoprostol in first-trimester medical abortion compared to misoprostol alone. Materials and Methods: It was a comparative observational study conducted at R. G. Kar Medical College, a tertiary care hospital in West Bengal, India. The study population was the antenatal mothers booked at antenatal clinic willing for termination of pregnancy at <12 weeks of gestational age. Participants were allocated, 39 in each group in a non-randomized manner. Patients in one group (Group A) were posted for medical abortion with combination regimen of tablet letrozole (10 mg) once daily for 3 days followed by application of tablet misoprostol 800 mcg sublingually on day 4. In other group (Group B), patients were on misoprostol-only regimen with the application of tablet misoprostol 800 mcg sublingually. Results: Induction-abortion time was significantly less in the letrozole group (11±0.79 h) than the misoprostol group (13.23±0.81 h), P=0.0001. Complete abortion rate was significantly higher in the letrozole group compared to misoprostol group (84.62% and 64.10%, respectively, P=0.03). 15.38% patients in the letrozole group and 35.90% patients in the misoprostol group had excessive vaginal bleeding and the difference was statistically significant, P=0.03. The duration of vaginal bleeding was also significantly less in the letrozole group (2.45±0.29 days) than the misoprostol group (2.82±0.37 days), P<0.0001. Incidence of side-effects was comparable and the severity of side-effects was not significantly different between the groups. Conclusion: Letrozole and misoprostol combination regimen leads to significant increase in complete abortion rate and also significant reduction of the duration of vaginal bleeding, induction-abortion time, and need for surgical intervention when compared to misoprostol regimen.